2017
DOI: 10.3389/fpsyg.2017.01493
|View full text |Cite
|
Sign up to set email alerts
|

A SEMantic and EPisodic Memory Test (SEMEP) Developed within the Embodied Cognition Framework: Application to Normal Aging, Alzheimer's Disease and Semantic Dementia

Abstract: Embodiment has highlighted the importance of sensory-motor components in cognition. Perception and memory are thus very tightly bound together, and episodic and semantic memories should rely on the same grounded memory traces. Reduced perception should then directly reduce the ability to encode and retrieve an episodic memory, as in normal aging. Multimodal integration deficits, as in Alzheimer's disease, should lead to more severe episodic memory impairment. The present study introduces a new memory test deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(10 citation statements)
references
References 76 publications
(90 reference statements)
0
10
0
Order By: Relevance
“…Disappearance of the von Restorff effect with perceptual distinctiveness (Vallet et al, 2017;Vitali et al, 2006) Diminished, but not abolished, benefit of memory for novel over familiarized items; related to hippocampal integrity (Lekeu et al, 2003) MCI: intact recognition memory for novel items (Belleville et al, 2011).…”
Section: Novelty-related Memory Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disappearance of the von Restorff effect with perceptual distinctiveness (Vallet et al, 2017;Vitali et al, 2006) Diminished, but not abolished, benefit of memory for novel over familiarized items; related to hippocampal integrity (Lekeu et al, 2003) MCI: intact recognition memory for novel items (Belleville et al, 2011).…”
Section: Novelty-related Memory Effectsmentioning
confidence: 99%
“…Furthermore, there was no correlation between sensitivity to novelty and overall memory performance, indicating that the absence of the novelty effect on memory was not related to the memory impairment itself. Recently, Vallet et al (2017) also showed that mild to moderate AD patients (MMSE range: 18-27) did not display better memory for isolated items (a small number of pictures presented on a yellow background) compared to nonisolated items (many pictures on a white background). In light of the retrieval cue hypothesis (Nairne, 2006), it may be that AD patients failed to benefit from the reduced interference linked to the novel retrieval cue compared to control items, possibly because less control items competed at retrieval.…”
Section: Novelty and Explicit Memory In Ad Novelty-related Memory Effectmentioning
confidence: 99%
“…This view is supported both by data coming from PD studies (Anders et al, ) and by recent data on the MCI/AD spectrum (Farina et. al., ; Moretti, ; Vallet et al, ).…”
Section: Conclusion and Perspectives: Future Directions For Clinical mentioning
confidence: 98%
“…Among the many aging phenomena, memory decline of varying degrees is the most commonly observed sign of dementia. Regardless of whether it is a healthy older adult or a person with a neurological disease, their earliest memory deterioration is usually an episodic memory deficit [ 8 ]. Due to the high correlation between perception and episodic memory, the decline in perception ability due to aging directly reduces the ability to encode and retrieve episodic memories.…”
Section: Introductionmentioning
confidence: 99%